2021
DOI: 10.1101/2021.02.24.21250288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental attitudes towards mandatory vaccination; a systematic review

Abstract: While mandatory vaccination schemes can increase vaccine uptake rates, they can also cause backlash among some parents. We conducted a systematic review investigating parental beliefs about vaccine mandates and factors associated with support for mandatory vaccination schemes. We searched Embase, Ovid MEDLINE, Global Health, APA PsycINFO and Web of Science from inception to 17th September 2020. Seventeen studies (five qualitative, twelve quantitative) were eligible for inclusion. We synthesised results of qual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Of the types of intervention that were the focus of 1 A recent systematic review of mandatory vaccination for children recently summarized findings as follows: 'Quantitative studies found little evidence for any factors being consistently associated with support for mandatory vaccination. Qualitative studies found that parents perceived mandatory vaccination schemes as an infringement of their rights and that they preferred universal, compared to targeted, schemes' [22] studies, 2 concerned test-negative result for current infectiousness, 14 concerned test-positive for antibodies conferring natural immunity, and 17 concerned vaccination(s) conferring immunity. The majority of studies related to Covid-19, with one concerning yellow fever, and one other concerning flu vaccinations.…”
Section: Search Resultsmentioning
confidence: 99%
“…Of the types of intervention that were the focus of 1 A recent systematic review of mandatory vaccination for children recently summarized findings as follows: 'Quantitative studies found little evidence for any factors being consistently associated with support for mandatory vaccination. Qualitative studies found that parents perceived mandatory vaccination schemes as an infringement of their rights and that they preferred universal, compared to targeted, schemes' [22] studies, 2 concerned test-negative result for current infectiousness, 14 concerned test-positive for antibodies conferring natural immunity, and 17 concerned vaccination(s) conferring immunity. The majority of studies related to Covid-19, with one concerning yellow fever, and one other concerning flu vaccinations.…”
Section: Search Resultsmentioning
confidence: 99%
“…'Quantitative studies found little evidence for any factors being consistently associated with support for mandatory vaccination. Qualitative studies found that parents perceived mandatory vaccination schemes as an infringement of their rights and that they preferred universal, compared to targeted, schemes' [23] . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…'Quantitative studies found little evidence for any factors being consistently associated with support for mandatory vaccination. Qualitative studies found that parents perceived mandatory vaccination schemes as an infringement of their rights and that they preferred universal, compared to targeted, schemes' [23] disease. We also included studies of public views of mandatory vaccination given that mandation can only be enforced with some kind of check -i.e.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%